A New Method for Wide-field Near-IR Imaging with the Hubble Space Telescope. (5th December 2016) - Momcheva, Ivelina G.; van Dokkum, Pieter G.; van der Wel, Arjen; Brammer, Gabriel B.; MacKenty, John; Nelson, Erica J.; Leja, Joel; Muzzin, Adam; Franx, Marijn
Abstract: We present a new technique for wide and shallow observations using the near-infrared channel of Wide Field Camera 3 (WFC3) on the Hubble Space Telescope ( HST ). Wide-field near-IR surveys with HST are generally inefficient, as guide star acquisitions make it impractical to observe more than one pointing per orbit. This limitation can be circumvented by guiding with gyros alone, which is possible as long as the telescope has three functional gyros. The method presented here allows us to observe mosaics of eight independent WFC3-IR pointings in a single orbit by utilizing the fact that HST drifts by only a very small amount in the 25 s between non-destructive reads of unguided exposures. By shifting the reads and treating them as independent exposures the full resolution of WFC3 can be restored. We use this "drift and shift" (DASH) method in the Cycle 23 COSMOS-DASH program, which will obtain 456 WFC3 H 160 pointings in 57 orbits, covering an area of 0.6 degree in the COSMOS field down to H 160  = 25. When completed, the program will more than triple the area of extra-galactic survey fields covered by near-IR imaging at HST resolution. We demonstrate the viability of the method with the first four orbits (32 pointings) of this program. We show that the resolution of the WFC3 camera is preserved, and that structural parameters of galaxies are consistent with those measured in guided observations.